2021
DOI: 10.1159/000518554
|View full text |Cite
|
Sign up to set email alerts
|

Positive Anti-GABAB Receptor Antibodies in a Patient with Hashimoto’s Thyroiditis and Bipolar Affective Disorder

Abstract: A kind of autoimmune encephalitis with positive autoantibodies toward the B1 subunit of the gamma-aminobutyric acid-type B receptor is known as anti-GABABR encephalitis. It is an autoimmune brain disorder with typical manifestations of a limbic encephalitis. It can coexist with positive anti-thyroid autoantibodies. We described a 57-year-old woman who was diagnosed with a bipolar affective disorder. The patient had high titers of anti-thyroid peroxidase antibodies, and she also was positive for anti-GABABR ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Thus, blood 25OHD levels reflect vitamin D status from both diet and sunlight exposure. 7 Numerous studies have confirmed associations between HT and trace elements such as iodine and selenium; [8][9][10][11] however, the association between HT and vitamin D remains debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, blood 25OHD levels reflect vitamin D status from both diet and sunlight exposure. 7 Numerous studies have confirmed associations between HT and trace elements such as iodine and selenium; [8][9][10][11] however, the association between HT and vitamin D remains debatable.…”
Section: Introductionmentioning
confidence: 99%